Improvements in Managemental and Therapeutic Approaches of Bovine Mastitis: A Review - Rahmati, Shahpoor (Journal of Natural Sciences – Kabul University, 2023)
Bovine mastitis caused by infectious agents remains a significant condition affecting dairy cattle, resulting in substantial economic losses globally. It is the most prevalent disease in dairy cattle, and routine diagnosis differentiates between its clinical and subclinical forms. Various therapeutic approaches, including antibiotics, bacteriophages, antimicrobial peptides, probiotics, herbal treatments, nutritional therapies, dry cow treatments, lactation therapies, and genetic selection, have been evaluated for their effectiveness. This review aims to identify bacterial causes of mastitis, assess their antibiotic sensitivity, and propose suitable solutions for its treatment and control. Mastitis adversely affects milk quality and animal health, leading to increased economic losses and higher culling rates in dairy production systems.